Unit A1 of HE “Pirot” Excitation System Parameter Identification - Joksimović, Dušan; Stojić, Đorđe; Ćirić, Zoran; Arnautović, Dušan; Milinković, Milan; Veinović, Slavko; Milojčić, Nemanja (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
In the paper, equivalent transfer function models of automatic and manual control of HE “Pirot” unit A1 excitation system are presented. All determined parameter values are shown and discussed. Using experimentally derived step response records of the excitation system, the equivalent model parameters are identified and compared to previously adjusted values. The reactive voltage drops at generator terminals, as well as at the HV side of the step-up transformer, are determined.